NATURALEZA Y SIGNIFICADO DE LAS GRANULACIONES LEUCOCITARIAS - GONZALEZ GUZMAN, IGNACIO (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1947)
Stained smears of aspirations of bone marrow of the white rat were studied for the various cellular types and their morph Examination was also made after supravital staining with neutral red and Janus green A particular characteristic in the rat is a te
BOL INST ESTUD MED BIOL
Keywords: NATURALEZA, GRANULACIONES, LEUCOCITARIAS; CIENCIAS MEDICAS; OTRAS ESPECIALIDADES MEDICAS (ESPECIFICAR); MEDICINA BIOQUIMICA